The impact of COVID-19 on BNP, NT-proBNP and ANP in heart failure: The impact of COVID-19 on BNP, NT-proBNP and ANP - Tawfeeq, Rawaz D.; Alwan, Mohammed H.; Ismael, Ava T.; Hamad, Badraldin K. (Cellular and Molecular Biology, 2023)
Extensive research has been conducted on biomarkers associated with coronavirus disease 2019 (COVID-19) in both healthy individuals and those with various conditions, particularly heart diseases. However, there is a limited investigation into the relationship between widely used cardiac biomarkers known as natriuretic peptides, including Brain natriuretic peptide (BNP), N-Terminal Pro-B-Type Natriuretic Peptide (NT-proBNP), and Atrial natriuretic peptide (ANP), and COVID-19 infection specifically in patients with heart failure. These natriuretic peptides assess the hemodynamic stress on the heart wall and have the potential to serve as biomarkers for evaluating the severity of COVID-19 infection in heart failure patients. Therefore, this study aimed to assess the plasma concentration of BNP, NT-proBNP, and ANP in a medium-sized cross-sectional case-control study involving 360 heart failure patients, both infected and uninfected with COVID-19. The heart failure patients were categorized into subgroups based on their Ejection Fraction (EF) percentage, namely heart failure with reduced EF (HFrEF), heart failure with mid-range EF (HFmrEF), and heart failure with preserved EF (HFpEF). Our findings demonstrate a significant increase in plasma levels of BNP and NT-proBNP in all heart failure patients, as well as in each subgroup (HFrEF, HFmrEF, and HFpEF) when infected with COVID-19, compared to uninfected heart failure patients. These established cardiac biomarkers have the potential to be utilized as future indicators for assessing the severity of COVID-19 infection in heart failure patients, thereby enhancing heart failure management and reducing irreversible cardiac damage.